2015
DOI: 10.1007/s00464-015-4279-6
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding colorectal resection for polyps: is CELS the best method?

Abstract: CELS and similar procedures are viable options for intestinal polyps removal. Moving forward, we suggest methods to standardize CELS procedure reporting. The reported outcomes of CELS indicate that it should be seen as a viable alternative to segmental resection when endoscopic methods alone do not suffice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 43 publications
0
18
0
3
Order By: Relevance
“…The colonoscopic-assisted laparoscopic resection involves endoscopic localisation of the polyp margins. Feasible preliminary data are promising: 70-87% of polyps not amenable to routine snare polypectomy can be successfully removed with these techniques [8,35,48].…”
Section: Combined Methods: Future Directionsmentioning
confidence: 99%
“…The colonoscopic-assisted laparoscopic resection involves endoscopic localisation of the polyp margins. Feasible preliminary data are promising: 70-87% of polyps not amenable to routine snare polypectomy can be successfully removed with these techniques [8,35,48].…”
Section: Combined Methods: Future Directionsmentioning
confidence: 99%
“…33 A recent systematic review includes 18 studies with a total of 532 patients. 36 EMR, ESD, and full-thickness excisions were performed heterogeneously throughout these studies. Successful CELS resections ranged from 58 to 100%, and studies with more than 20 patients demonstrated higher success rates (74-91%).…”
Section: Recent Literaturementioning
confidence: 99%
“…[38][39][40] Some surgeons choose to use a laparoscopic bowel clamp at the terminal ileum, or just proximal to the lesion. 34,36 However, others have found this to be an unnecessary step when using CO 2 endoscopy. 33,38 EMR versus ESD versus Full-Thickness Resection…”
Section: Intraoperative Colonoscopymentioning
confidence: 99%
See 2 more Smart Citations